Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.stem.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neural Stem Cells from the Subventricular Zone Give Rise to Reactive Astrocytes in the Cortex after Stroke

Abstract: Reactive astrocytes (RAs) have been reported to convert to multipotent neural stem cells (NSCs) capable of neurosphere (NS) formation and multilineage differentiation in vitro. Using genetic tagging, we determined that subventricular zone (SVZ) NSCs give rise to NSs derived from the stroke-injured cortex. We demonstrate that these cells can be isolated from the cortex in two different models of stroke and from different stroke-lesioned cortical regions. Interestingly, SVZ NSCs give rise to a subpopulation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
206
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(219 citation statements)
references
References 63 publications
(89 reference statements)
2
206
0
2
Order By: Relevance
“…Interestingly, this proliferative population of reactive astrocytes was also shown by clonal analysis to be derived from distinct progenitors 20 , suggesting that one source of reactive astrocyte heterogeneity may be distinct cellular origins. In support of this, neural stem cell (NSC)-derived reactive astrocytes have been shown to contribute to glial scars in the brain 21 , while a recent study found little contribution of NSC-derived reactive astrocytes to SCI-induced glial scars 22 . Therefore, reactive astrocyte heterogeneity is dependent on the site of injury.…”
Section: Functional Diversity Of Glial Cells In the Injured Cnsmentioning
confidence: 99%
“…Interestingly, this proliferative population of reactive astrocytes was also shown by clonal analysis to be derived from distinct progenitors 20 , suggesting that one source of reactive astrocyte heterogeneity may be distinct cellular origins. In support of this, neural stem cell (NSC)-derived reactive astrocytes have been shown to contribute to glial scars in the brain 21 , while a recent study found little contribution of NSC-derived reactive astrocytes to SCI-induced glial scars 22 . Therefore, reactive astrocyte heterogeneity is dependent on the site of injury.…”
Section: Functional Diversity Of Glial Cells In the Injured Cnsmentioning
confidence: 99%
“…Some reactive astrocytes in peri-infarct areas may arise from the neural stem cells in the subventricular zone. 39 The fact that neural stem cell-derived or immature astrocytes, which express nestin, 33 synthesize less chondroitin sulfate proteoglycans that inhibit axonal growth may support the beneficial effects of peri-infarct astrogliosis in acute ischemic stroke. 21 Moreover, recent evidence suggests that white matter reorganization also participates in poststroke recovery in periinfarct areas.…”
Section: Tachibana Et Al Effects Of Reperfusion In Brain Ischemia 2229mentioning
confidence: 99%
“…This age effect on OPC and white matter responses appears to be mediated by greater local inflammation in the aged brain81 and by intrinsic differences in aged OPCs 82. In another aspect of gliogenesis, stroke induces proliferation of astrocytes adjacent to the lesion,83, 84 and a remarkable generation of new astrocytes from neural progenitor cells that migrate from the subventricular zone 85, 86. Astrocytes proliferate near human stroke,87 but the role of this generation of new astrocytes immediately adjacent to stroke in recovery remains to be defined.…”
Section: The Brain Forms Regenerative Cellular Niches During Repair Amentioning
confidence: 99%